Keadilan Hukum dalam Pasal 6 UU No. 12 Tahun 2022 dan Perlindungan Islam dalam HR. At-Thabrani No. 486 Terhadap Kasus Kekerasan Seksual - Sonia, Gina; Arifin, Tajul (TAFAQQUH, 2025)
Sexual violence is a violation of human rights, and no one has the right to violate someone's human rights. According to data from the Ministry of Women's Empowerment and Child Protection, thousands of people, including women, men, and children, have become victims of sexual violence. This issue requires attention from society and law enforcement agencies to create a safe space for victims of sexual violence. The purpose of this article is to raise awareness about the many survivors of sexual violence who need justice and protection, both in the eyes of the law and in the eyes of religion. This research uses a descriptive analytical method to describe and analyze the legal phenomenon of sexual violence in society. This article proves that Article 6 of Law No. 12 of 2022 can provide justice for victims, and Islam can be a protector, as seen in HR. At-Thabrani No. 486.